Transforming food security and safety: the role of earth Intelligence in global food systems - Jampani, Mahesh; Lau, A.; Aydin, O. (The Group on Earth Observations (GEO), 2025)
Every meal relies on a healthy planet. Yet in 2024, between 638 and 720 million people went hungry (according to the 2025 State of Food Security and Nutrition in the World Report), while climate change, polluted water, and intensive farming are making our food less safe. Earth Intelligence helps us see risks early, test scenarios, and act before problems escalate. Within the One Health approach, it connects the dots between humans, animals, and environment so that policymakers and practitioners can boost food security, and protect both public and planetary health.